G470 Preterm-born males display a diurnal cortisol profile at 2 years characteristic of early adversity. (24th May 2017) - Hurrion, EM; Harris, M; Greer, RM; Grey, PH
Abstract : Aims: To investigate the diurnal cortisol profile at 2 years of age of preterm compared with term born children. Methods: Preterm infants (24–30weeks), n=82, and term controls (37–41weeks), n=61, were recruited from a longitudinal study. At 2 years corrected age participants underwent assessment using Bayley III Scales of Infant and Toddler Development (Bayley-III), and parents completed Child Behaviour Checklist (CBCL). Prior to the assessment, parents collected same-day waking and bedtime saliva samples at home using dental swabs. Saliva was extracted and cortisol concentration measured using a commercially-available enzyme immunoassay kit. Results: There was a statistically significant difference between diurnal cortisol values of preterms compared with terms, which was accounted for entirely by male infants (table). Male preterms had lower waking and bedtime values, and a smaller difference between waking and bedtime values ('flattened profile'). These findings were greater for extremely preterm males (<28 weeks). Collection times between groups were almost identical, and univariate analysis of many demographic and psychosocial variables did not reveal any convincing modifying factor other than maternal depression and bedtime cortisol value. Table of diurnal cortisol values by preterm status and gender. There was no association between diurnal cortisol values and cognitive/language performance on Bayley-III, or attentional problems on CBCL. Conclusion: Preterm-born males display a diurnal cortisol profile characteristic of early adversity, consistent with perinatal programming from a highly stressful NICU environment. No convincing confounding variable was found that explained this association. Preterm-born females appear to be protected from this effect, consistent with sexual dimorphism seen in many studies of perinatal programming of the HPA axis. The known association of this diurnal pattern with later adverse behavioural and mental health outcomes is concerning.